Higher propensity of Wharton's jelly derived mesenchymal stromal cells towards neuronal lineage in comparison to those derived from adipose and bone marrow. (18th February 2013) - Balasubramanian, Sudha; Thej, Charan; Venugopal, Parvathy; Priya, Nancy; Zakaria, Zubaidah; SundarRaj, Swathi; Majumdar, Anish Sen
Abstract Mesenchymal stromal cells (MSCs) derived from different tissue sources are capable of differentiating into neural and glial cell types. However, the efficiency of differentiation varies between MSCs derived from different tissues. We compared the efficiency of neural progenitor population generation between adipose (AD), bone marrow (BM) and Wharton's jelly (WJ) derived MSCs. MSCs isolated from the three sources were induced to form primary neurospheres using epidermal growth factor (20 ng/mL) and bFGF (20 ng/mL). The self‐renewal potential of the primary neurospheres was assessed by secondary neurosphere assay. Primary neurospheres were differentiated to neuronal lineage on fibronectin‐coated dishes. The neurospheres and the resulting differentiated cells were characterized by immunocytochemistry and the RT‐PCR analyses. We have also investigated the secretome profile of neuronal‐related growth factors using Ray biotech cytokine array. The results show that MSCs from the three sources can be induced to generate neurospheres and they expressed neural progenitor markers nestin, Sox2 and Pax6 transcription factors. When differentiated on fibronectin coated dishes in mitogen free culture conditions, the primary spheres from all three sources were able to generate neuron/glial ‐ like cells which expressed Nfl, Map2 and GFAP with varied efficiency. Self‐renewal potential of these progenitors was determined by secondary sphere formation. WJ‐ and BM‐derived neurospheres were able to self‐renew, while AD derived progenitors failed to do so. Comparison of the secretome profile suggested that WJ derived MSCs secrete more neurotrophic factors. The data suggest that human WJ derived MSCs can be induced to make neural progenitors with higher efficiency compared to BM and AD derived MSCs.